Biodiversity of sea slugs and shelled relatives (Mollusca: Gastropoda) of the Cretan Archipelago (Greece), with taxonomic remarks on selected species. (10th December 2015) - Crocetta, Fabio; Poursanidis, Dimitrios; Tringali, Lionello Paolo
Abstract: To date, the knowledge of the biodiversity of Cretan Archipelago sea slugs and shelled relatives is poor in comparison to other parts of the Greek seas and to the Mediterranean Sea in general. Based on an extensive review of literature data, complemented by recent field observations, we provide an updated checklist of 81 taxa from the Cretan Archipelago, 11 of which constitute new records. Careful attention has been given to molluscan species described from the area (four taxa, two of which valid), as well as to doubtful records (five taxa). Finally, taxonomic remarks are offered for Bulla vestita Philippi, 1840, Cylichna parvula Jeffreys, 1883 and Bulla girardi Audouin, 1826. B. vestita has priority over Bulla retifer Forbes, 1844, that is definitively considered a junior synonym of the former. C. parvula is redescribed, changed of family (from Cylichnidae H. Adams & A. Adams, 1854 to Retusidae Thiele, 1925), first moved to the genus Retusa T. Brown, 1827 and compared with similar congeneric species. Within this framework, we also figure a syntype of Cylichna laevisculpta Granata-Grillo, 1877 for the first time. Finally, the attribution of B. girardi to the genus Ventomnestia Iredale, 1936 is discussed and its establishment status in Greece is re-evaluated. The present paper lays the foundations to extend local studies on sea slugs and shelled relatives and fills some expected gaps in the Mediterranean distribution of several taxa. It therefore constitutes a mandatory step when providing large-scale and well-defined Mediterranean molluscan distributional patterns, and emphasizes the necessity of more intensive studies of the molluscan communities in the area.